Human development - Crandell, Thomas L.; Crandell, Corinne Haines; Vander Zanden, James W. (New York : McGraw-Hill, 2009)
In the three years that have passed between the eight edition and the ninth edition of our text-book, there has been an astonishing, rapid change in the models, concept, and research information used to study human development.
Part One. the study of human development -- Part Two. beginnings -- Part Three. birth and infancy: the first two years -- Part Four. early childhood: 2 to 6 -- Part Five. middle childhood: 7 to 12 -- Part Six. adolescence -- Part Seven. early adulthood -- Part Eight. middle childhood -- Part Nine. late adulthood -- Part Ten. the end of life.
Includes bibliographical references and index.
Keywords: PSYCHOLOGY; DEVELOPMENTAL PSYCHOLOGY